Exploring the interrelation between process management and organizational culture: A critical review - Corinna Grau; Jürgen Moormann (Frankfurt School of Finance & Management, 2013)
Managing the business processes of a company is a task which has emerged as a top priority across all industries. However, business process management (BPM) is not just a set of structured methods and technologies which can simply be assigned to employees. In contrary, the success of any process initiative is interwoven with the culture of the respective company. In addition, in most cases there is not only one organizational culture but often a range of subcultures within an organization due to previous mergers, existing subsidiaries etc. Despite its importance, the interrelation between BPM and organizational culture has been only sparsely explored. This paper analyzes and determines the status quo of academic literature concerning the interrelation between BPM and organizational culture. The results reveal considerable differences in the perception of the interface between both fields. Furthermore, our analysis shows that the organizational psychological perspective has been widely neglected in process management literature. To the best of our knowledge, this is the first literature review written from both a process management and an organizational psychological perspective. As such, it strives to contribute to a comprehensive and thorough understanding of this interrelation. Based on the review we develop a framework, serving as a basis for a deeper understanding of the interdependency and providing avenues for future research.
Keywords: L20; M10; M14; 330; Business Process Management (BPM); Organization; Organizational culture; Organizational psychology; Process